2002
DOI: 10.1023/a:1021227019915
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ocular complications of Behçet's disease can be severe and lead to blindness in 90% of untreated patients. We aimed to evaluate the long-term use of low dose cyclosporin-A (CsA) which is a potent immunomodulatory agent in the treatment of ocular Behçet's disease. Fifty-two patients (104 eyes) with ocular Behçet's disease using CsA for at least 1 year were included in this study. All the patients underwent complete ophthalmological and systemic examination. Five mg/kg/per day CsA was started to the patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Previous studies reported similar or inferior effectiveness of cyclosporine for ocular inflammatory disease compared to our study [2,6-9,12-14,17,20,21,26]. This disparity comes from the differences in outcome measures and the definition of success in uveitis control, thus making direct comparison between studies impossible.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Previous studies reported similar or inferior effectiveness of cyclosporine for ocular inflammatory disease compared to our study [2,6-9,12-14,17,20,21,26]. This disparity comes from the differences in outcome measures and the definition of success in uveitis control, thus making direct comparison between studies impossible.…”
Section: Discussioncontrasting
confidence: 69%
“…Only a small group of patients in our study discontinued cyclosporine due to toxicity, which is superior to other studies that reported adverse effects with low-dose cyclosporine for ocular inflammation [17,20,21,27]. We used a protocol of relatively rapid cyclosporine dose reduction according to inflammation status, which might have also contributed the lower rates of toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Visual acuity 9,15,16,120,144-196,252-254 and inflammatory attacks9,15,120,144,147,155-158,161,162,164,165,166,169,170,171,173,176,181,183,184,186,188-196 are the most widely used outcome measures. However, the definition of an inflammatory flare varied widely among studies, and visual acuity was reported in several different ways, including change on Snellen chart or Japanese standard Landolt visual acuity chart, calculating the LogMar (logarithm of the minimum angle of resolution), or the percentage of patients who had a certain level of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclosporine has been observed to be particularly effective in patients with Behçet's disease-associated uveitis [25]; in children with juvenile idiopathic arthritis-associated uveitis, cyclosporine is more effective when used in combination with methotrexate [26]. Initial dosing is recommended at 3-5 mg/kg/day divided into two doses, followed by a maintenance dose of 2-3 mg/kg/day [6,27].…”
Section: Treatmentmentioning
confidence: 99%